Psychometric properties of the German version of the Clinician-Administered PTSD Scale for DSM-5 (CAPS-5) in clinical routine settings: study design and protocol of a multitrait–multimethod study. Issue 6 (22nd June 2020) - Spies, Jan-Peter; Woud, Marcella Lydia; Kessler, Henrik; Rau, Heinrich; Willmund, Gerd Dieter; Köhler, Kai; Herpertz, Stephan; Blackwell, Simon E; Bovin, Michelle; Marx, Brian P; Cwik, Jan Christopher
Abstract : Introduction: The aim of this study is to investigate the diagnostic accuracy, psychometric properties and clinical utility of the German version of the Clinician-Administered Post-Traumatic Stress Disorder (PTSD) Scale for Diagnostic and Statistical Manual of Mental Disorders-5 (DSM-5) (CAPS-5) in routine clinical settings. Methods and analysis: This study is a non-interventional, multitrait–multimethod design, multicentre study that will be carried out at German civil and military inpatient and outpatient clinics. A total sample size of n=219 participants who have experienced at least one traumatic event according to criteria as defined in the DSM-5 will be recruited. For the investigation of the diagnostic accuracy and clinical utility of the CAPS-5, participants will be categorised into one of three groups, depending on their traumatic experiences and post-traumatic symptomatology: (1) monotraumatisation with PTSD; (2) multiple traumatisation with PTSD and (3) traumatisation without PTSD. Interviews will be conducted face to face by interviewers in routine clinical settings. All participants will also be asked to complete a comprehensive set of questionnaires in order to investigate different facets of construct validity and clinical utility. First, differences between all three groups in CAPS-5 sum and subscale scores will be investigated. Test–retest reliability and inter-rater reliability will be determined. Internal consistency will be calculated using structural equation modeling (SEM) based internal consistency coefficients. Construct validity will be measured with Spearman's rank correlation analyses and multivariate analyses of variance with Holm-Bonferroni corrected post hoc analysis of variances. In order to test diagnostic accuracy, receiver operating characteristics and sensitivity and specificity analyses will be conducted. The model structure of the German CAPS-5 will be analysed using confirmatory factor analyses. Ethics and dissemination: The study received ethical approval by the Ethics Committees of the Faculty of Psychology at the Ruhr-Universität Bochum (reference numbers: 331 and 358). The results of the study will be presented nationally and internationally at scientific conferences and will be published in scientific journals. Trial registration number: DRKS00015325